Some biological, behavioral and social aspects of the perfumery use in the Ukrainian population sample (Part 2. Education level associations) - Filiptsova, Olga; Naboka, Olga; Bobro, Svitlana; Bashura, Olexander; Osypenko, Yuliia (ScienceRise: Biological Science, 2023)
The aim. The study represents a continuation of the previous one, and provide various aspects related to the use of perfumery, which can be characterized by certain associations with the education level of Ukrainian consumers. Factors that have direct or indirect biological and medical significance and, accordingly, may have a potential impact on the safety of the perfume products use by humans, were selected for the analysis. Materials and methods. The analysis included information about 124 individuals living in Ukraine. The respondents answered the questions of the questionnaire developed regarding some aspects of the perfumery use. The Pearson chi-squared (χ2) test was used to analyze the relationships between qualitative characteristics. Results and discussion. Most of the studied aspects related to the perfumes use demonstrate associations, caused by the dependence of the education level on age. The analysis revealed that individuals with any education most often (about half of the cases or more) choose a perfume based on its scent. The study showed that the majority of respondents believe that the price of a perfume depends on a combination of factors, namely the composition of the products, the brand and the cost of the packaging. More than 80 % of people, regardless of the education level, believe that the persistence of a perfume is definitely a sign of quality. The most common opinion among people of all education levels was that non-original perfumes can have a more negative effect on people's health than original products. The "lipstick effect" in relation to perfume products (demand for items of "affordable luxury" in times of economic crises and wars) was observed. Conclusions. The study supplemented the previously found associations of age and some biological and behavioral aspects of perfume use among the population of Ukraine with data on the presence or absence of such associations in relation to the education level